2001
DOI: 10.1242/dev.128.24.5031
|View full text |Cite
|
Sign up to set email alerts
|

Slit proteins are not dominant chemorepellents for olfactory tract and spinal motor axons

Abstract: Members of the Slit family are large extracellular glycoproteins that may function as chemorepellents in axon guidance and neuronal cell migration. Their actions are mediated through members of the Robo family that act as their receptors. In vertebrates, Slit causes chemorepulsion of embryonic olfactory tract, spinal motor, hippocampal and retinal ganglion cell axons. Since Slits are expressed in the septum and floor plate during the period when these tissues cause chemorepulsion of olfactory tract and spinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The 170-kDa band was in agreement with the predicted size of the full-length hSlit3 (167.7 kDa) and the 120-kDa band would correspond to the N-terminal fragment, suggesting that the cleavage of hSlit3 generates an 50-kDa C-terminal fragment. A similar cleavage occurred in hSlit2 and hSlit3 expressed in CHO cells (Patel et al 2001), and hSlit2 and dSlit expressed in COS and HEK 293 cells (Brose et al 1999). A putative cleavage site was proposed for hSlit2 (Brose et al 1999).…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…The 170-kDa band was in agreement with the predicted size of the full-length hSlit3 (167.7 kDa) and the 120-kDa band would correspond to the N-terminal fragment, suggesting that the cleavage of hSlit3 generates an 50-kDa C-terminal fragment. A similar cleavage occurred in hSlit2 and hSlit3 expressed in CHO cells (Patel et al 2001), and hSlit2 and dSlit expressed in COS and HEK 293 cells (Brose et al 1999). A putative cleavage site was proposed for hSlit2 (Brose et al 1999).…”
Section: Resultsmentioning
confidence: 62%
“…Expression of recombinant HSCF Slit3 has been observed to be cleaved to give rise to N-and C-terminal fragments in vivo (Patel et al 2001). We recently examined the biological function of a recombinant N-terminal fragment of hSlit3 and observed that the N-terminal fragment potently promotes angiogenesis (Zhang et al 2009), but the biological function of the C-terminal fragment has not been determined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These in vitro data suggested that fibroblast and vascular mural cell–mediated SLIT3 can stimulate cardiomyocyte hypertrophy. As SLITs can be cleaved into N- and C-terminal fragments in vivo, 49 we next investigated which portion of SLIT3 was responsible for stimulating cardiomyocyte hypertrophy because these fragments have been determined to bind to different receptors. 26 , 30 We cultured NRCMs with recombinant N- and C-terminal fragments of SLIT3 (SLIT3-NT and SLIT3-CT, respectively) and observed that only SLIT3-NT could promote the transcription of Nppa and Nppb and stimulate NRCMs hypertrophy ( Figure S5K through S5M ).…”
Section: Resultsmentioning
confidence: 99%
“…Slit guidance ligand 2 (Slit2), a chemoattractant or chemorepellent dependent on the isoform, and activation of Roundabout receptor (Robo1), a coreceptor of Slit2, induces chemorepulsion of axons as well as neutrophils (Hu, 1999;Nguyen Ba-Charvet et al, 1999;Park et al, 2016). Slit1 and Slit3 also induce chemorepulsion of olfactory tract and spinal motor axons during development (Patel et al, 2001).…”
Section: Several Proteins Act As Neuronal Chemorepellentsmentioning
confidence: 99%